GPX4 deficiency-dependent phospholipid peroxidation drives motor deficits of ALS - Long-Fang Tu; Tian-Ze Zhang; Yang-Fan Zhou; Qing-Qing Zhou; Hai-Biao Gong; Lei Liang; Lin-Na Hai; Nan-Xin You; Yang Su; Yong-Jun Chen; Xu-Kai Mo; Chang-Zheng Shi; et al. (Journal of Advanced Research, 2023)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by oxidative stress that triggers motor neurons loss in the brain and spinal cord. However, the mechanisms underlying the exact role of oxidative stress in ALS-associated neural degeneration are not definitively established. Oxidative stress-generated phospholipid peroxides are known to have extensive physiological and pathological consequences to tissues. Here, we discovered that the deficiency of glutathione peroxidase 4 (GPX4), an essential antioxidant peroxidase, led to the accumulation of phospholipid peroxides and resulted in a loss of motor neurons in spinal cords of ALS mice. Mutant human SOD1G93A transgenic mice were intrathecally injected with neuron-targeted adeno-associated virus (AAV) expressing GPX4 (GPX4-AAV) or phospholipid peroxidation inhibitor, ferrostatin-1. The results showed that impaired motor performance and neural loss induced by SOD1G93A toxicity in the lumbar spine were substantially alleviated by ferrostatin-1 treatment and AAV-mediated GPX4 delivery. In addition, the denervation of neuron-muscle junction and spinal atrophy in ALS mice were rescued by neural GPX4 overexpression, suggesting that GPX4 is essential for the motor neural maintenance and function. In comparison, conditional knockdown of Gpx4 in the spinal cords of Gpx4fl/fl mice triggered an obvious increase of phospholipid peroxides and the occurrence of ALS-like motor phenotype. Altogether, our findings underscore the importance of GPX4 in maintaining phospholipid redox homeostasis in the spinal cord and presents GPX4 as an attractive therapeutic target for ALS treatment.